Effect of the time of carbohydrate intake on muscle glycogen recovery post-exercise - Ouchi, S.; Shiose, K.; Osawa, T.; Motonaga, K.; Kamei, A.; Kawahara, T.; Taguchi, M.; Takahashi, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Muscle glycogen synthesis rate is lowered when post-exercise CHO ingestion is delayed 2 hours compared with CHO ingestion immediately post-exercise. However, effect of CHO intake at 1 hour post-exercise on muscle glycogen recovery, is not clear. The purpose of this study was to evaluate the effect of the time of CHO intake on post-exercise muscle glycogen recovery. Six male endurance-trained athletes (age: 21±2 y; height: 170±8 cm; body mass: 61.3 ± 5.7 kg) consumed CHO (2.0 g/kg body weight) either immediately post-exercise (P-EX) or 60 minutes post-exercise (60P-EX) after a time trial (TT) on a cycle ergometer at 70% maximum power for approximately 60 min (842 ± 50 kJ). They were directed to complete the TT as soon as possible. The glycogen contents of thigh muscle group of the right leg: the vastus lateralis and vastus intermedius muscles were measured by carbon magnetic resonance spectroscopy (13C-MRS) before exercise and post-exercise, at 1, 2, 3, and 4 hours after exercise. Plasma glucose, insulin, and free fatty acid concentrations were also measured at the same time points. The TT times were 67.7±3.6 minutes for P-EX, and 65.8±5.4 minutes for 60P-EX. Muscle glycogen levels were decreased by exercise to 54.8 ± 2.4 % of pre-exercise levels for P-EX, and recovered to 68.0 ± 1.5 % of pre-exercise levels 4 hours after exercise for 60P-EX. At 1 h after exercise, the recovery rate of muscle glycogen was higher for P-EX than for 60P-EX (P < 0.05). At the other time points, there was no difference between P-EX and 60P-EX for the muscle glycogen recovery. Increased plasma glucose levels were more frequent for P-EX compared with 60P-EX at 1-2 hours after exercise (P < 0.05), and at 3 hours after exercise, for 60P-EX. Insulin levels were higher for P-EX compared with 60P-EX at 1 hour (P < 0.05), and for 60P-EX compared with P-EX at 3 hours (P < 0.01). Increased levels of plasma free fatty acids were observed for 60P-EX compared with P-EX at 1 hour after exercise (P < 0.05), and for P-EX compared with 60P-EX at 4 hours (P < 0.01). In conclusion, increased muscle glycogen recovery occurs 1 hour post-exercise when CHO intake is immediately after exercise, compared with a 60-minute delay; however, 4 hours after exercise, the influence of the timing of CHO intake is small.